2022
DOI: 10.1051/0004-6361/202142320
|View full text |Cite
|
Sign up to set email alerts
|

The Lensed Lyman-Alpha MUSE Arcs Sample (LLAMAS)

Abstract: Aims. We present the Lensed Lyman-Alpha MUSE Arcs Sample (LLAMAS) selected from MUSE and HST observations of 17 lensing clusters. The sample consists of 603 continuum-faint (-23 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 105 publications
(157 reference statements)
3
14
0
Order By: Relevance
“…One possible solution to solve this puzzle is through the study of strongly lensed LAEs (e.g. Swinbank et al 2007 ;Karman et al 2015 ;Caminha et al 2016 ;Patr ício et al 2016 ;Vanzella et al 2016Vanzella et al , 2020Smit et al 2017 ;Claeyssens et al 2019Claeyssens et al , 2022Chen et al 2021 ;Iani et al 2021 ). In fact, both lensing effects of magnification and stretching can allow to reach faint fluxes and small scales in short observing time, even though robust lensing models have to be developed in order to correctly interpret and compare the results.…”
mentioning
confidence: 99%
“…One possible solution to solve this puzzle is through the study of strongly lensed LAEs (e.g. Swinbank et al 2007 ;Karman et al 2015 ;Caminha et al 2016 ;Patr ício et al 2016 ;Vanzella et al 2016Vanzella et al , 2020Smit et al 2017 ;Claeyssens et al 2019Claeyssens et al , 2022Chen et al 2021 ;Iani et al 2021 ). In fact, both lensing effects of magnification and stretching can allow to reach faint fluxes and small scales in short observing time, even though robust lensing models have to be developed in order to correctly interpret and compare the results.…”
mentioning
confidence: 99%
“…Erb et al (2019) explained the offset by a significant variation of the neutral hydrogen column density across the object. Chen et al (2021) identified 2 Lyα nebulae spatially offset from the associated star-forming regions, suggesting large spatial fluctuations in the gas properties (see also Claeyssens et al 2022). Borisova et al (2016) found no evidence for "bipolar ionization cone illumination" patterns in their study of Lyα nebulae around quasars, except for one quasar (see their Section.…”
Section: Origin Of the Double-core Lyα Morphologymentioning
confidence: 94%
“…A similar consideration can be applied to the centroid/peak difference between the Lyman-α and the UV galaxy emission, supposing that the UV light is traced by the afterglow position. Indeed Claeyssens et al (2022) report a centroid/peak difference of several kiloparsecs. However, the velocity shift is extremely high if the Lyman-α emission comes from the same galaxy producing the absorption lines (even supposing a shift between the absorption line and the systemic redshift of the galaxy).…”
Section: Galaxy Structure and Kinematicsmentioning
confidence: 99%